2022
DOI: 10.3390/antibiotics11060805
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Effectiveness and Optimal Dosage of Favipiravir for Treatment of COVID-19: Results from a Multicenter Observational Study in Thailand

Abstract: Favipiravir is a broad-spectrum oral antiviral agent that shows in vitro activity against SARS-CoV-2. Presently, data on the real-world effectiveness and optimal dosage of favipiravir for treating COVID-19 are limited. We conducted a retrospective observational study of hospitalized adult patients with COVID-19 at five tertiary care hospitals in Thailand. We reviewed patient charts to obtain all necessary data. Among 247 COVID-19 patients, 63 (23.0%) received ≥1 dose of favipiravir. Of these 63 patients, 61.9%… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This has posed a need for vital scientific breakthroughs, which include innovative approaches to developing vaccines and antiviral drugs. The Japanese anti-influenza drug favipiravir [ 13 , 14 , 15 , 16 , 17 , 18 ] has shown promising results in the treatment of the disease in China, India, Russia and other countries [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ], either alone [ 26 , 27 , 28 , 29 , 30 ] or in combination [ 31 , 32 , 33 , 34 , 35 , 36 ] with other antiviral compounds.…”
Section: Introductionmentioning
confidence: 99%
“…This has posed a need for vital scientific breakthroughs, which include innovative approaches to developing vaccines and antiviral drugs. The Japanese anti-influenza drug favipiravir [ 13 , 14 , 15 , 16 , 17 , 18 ] has shown promising results in the treatment of the disease in China, India, Russia and other countries [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ], either alone [ 26 , 27 , 28 , 29 , 30 ] or in combination [ 31 , 32 , 33 , 34 , 35 , 36 ] with other antiviral compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective observational study, patients treated with favipiravir exhibited a Day-7 clinical improvement rate of 66% and a 4.8% 28-day mortality rate. 16 Real-world data analysis in Thailand demonstrated that favipiravir monotherapy outperformed supportive treatment, shortening recovery time in early symptomatic COVID-19 patients and reducing the 28-day mortality risk in severe COVID-19. 17 Whereas, in mild to moderate COVID-19, there was no difference in the time to sustained clinical recovery between patients who received favipiravir compared with placebo.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this panel is to generate a consensus on the use of Favipiravir in Mexican patients with COVID 19 infection, identifying needs and opportunities in the universe of patients who to date do not have established guidelines or standard treatment present in the country. Identifying the group of patients who can benefit from antiviral treatment in the early stage and reduce the morbidity and mortality presented in the pandemic [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%